Indian culture as a peculiar experience of cultural identification - O. V. Shynkarenko (Ukrainian Cultural Studies, 2021)
The article is dedicated to the consideration of the phenomenon of India as an indicative example of the productivity of the spiritual and ideological potential immanent in its historical heritage and social practices, as the basis of the identification process as an affirmation of unity for such a culturally diverse region. The bringing to light of the cultural identity of India, reconstructed at one time in the research of the patriotic intellectual elite, has become that productive self-determination ("the discovery of India"), which, having played its role in preserving its authenticity under foreign cultural pressure, remains relevant for successful self-development in complex globalization processes of multicultural world community. The principles of "synthesis, assimilation, development", "search for truth in a non-violent way", "unity in diversity" became the cultural codes that make up the core of the identification of the Indian cultural community. Through the actualization of the ancient spiritual tradition, the Indian reformers realized the inherent in the Indian philosophical and spiritual tradition the ability to synthesize, on the one hand, with the cultural layer of the past, and, on the other hand, with those innovations, albeit another cultural, even opposite (European Christian tradition, rationalism) , which, under the condition of tolerant, without vain denial, perception (assimilation of experience, models of other peoples who came to the subcontinent), productively complemented the cultural capacity of India. The modern large-scale globalization of socio-cultural life accentuate the importance of the problem of cultural identification as a process not only of individual identification (identity) with the world of one’s community, but also of collective self-determination in the formation and preservation of a unique cultural whole. The threat of erosion of meaningful semantic, value, symbolic orientations of unity actualize cultural studies of this problem. The culture of India provides a vivid experience of long-term preservation of the cultural integrity known for its ethnocultural diversity, the complex socio-historical conditions of the region’s existence, which appears to be very productive both for theoretical studies of cultural regionalism and for further cultural studies of identification.